Aproveitamento da casca de arroz para fabricação de chapas aglomeradas - Souza, Joel Telles de (2012)
Rice husk, waste produced by processing of rice, has become a problem of environmental, economic and public health. As a result, this research aims to explore the potential of these underutilized resources in Brazil in the development of particleboard glued with tannin-formaldehyde. Therefore, panels were manufactured with rice husk compacted at different density (0.65, 0.95 and 1.15 g/ cm³), levels of adhesives (7, 10 and 13%) and particles types (natural and processed), totaling 54 panels. The physical tests performed were moisture content, density, water absorption and thickness swelling and mechanical were static bending, screw withdrawal and internal bond. In order to complement the study, there were conducted biological tests for resistance to decay fungi Trametes versicolor and Gloephyllum trabeum. The results were analysed by for simple correlation and regression. In general, the use of rice hulls provided a reduction in strength of the compared to those made with wood particles. All particleboard were below the minimum standards in physical and mechanical tests; only the panels with 13% resin provided minimum values required by market standards regarding dimensional stability. The best performance of the panels developed in this work was found in biological tests. According to the criteria of the american standard, all treatments were classified as resistant to the fungus Trametes versicolor to white rot. In fungus Gloeophyllum trabeum (brown rot), most treatments were classified as moderately resistant. Therefore, this raw material, has proven to be an alternative with great potential for making panels for greater resistance to decay fungi.